2014
DOI: 10.1097/inf.0000000000000366
|View full text |Cite
|
Sign up to set email alerts
|

Otitis Media in Indonesian Urban and Rural School Children

Abstract: In Indonesia, the prevalence of CSOM is relatively high with most disease occurring in rural areas. The high rates in rural Bali with early progression to tympanosclerosis suggest a significant burden of potentially vaccine preventable illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 33 publications
3
31
1
3
Order By: Relevance
“…[ 13 ] In Indonesia, the prevalence of CSOM is relatively high with most disease occurring in rural areas; of the 7005 children studied, 116 (1.7%) had CSOM. [ 5 ] The rates per 1000 of CSOM in rural Bali and Bandung were significantly higher (75 and 25, respectively) than in the rest of Indonesia ( P < 0.05). In rural Bali the rate per 1000 children of inactive CSOM was 63 in 6-9 year olds, compared with 37 in children aged 13-15 years.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[ 13 ] In Indonesia, the prevalence of CSOM is relatively high with most disease occurring in rural areas; of the 7005 children studied, 116 (1.7%) had CSOM. [ 5 ] The rates per 1000 of CSOM in rural Bali and Bandung were significantly higher (75 and 25, respectively) than in the rest of Indonesia ( P < 0.05). In rural Bali the rate per 1000 children of inactive CSOM was 63 in 6-9 year olds, compared with 37 in children aged 13-15 years.…”
Section: Discussionmentioning
confidence: 98%
“…In rural Bali the rate per 1000 children of inactive CSOM was 63 in 6-9 year olds, compared with 37 in children aged 13-15 years. [ 5 ] Most studies have found that males and females are equally affected, although some have found a male predominance. [ 14 15 16 ] In our study, though male preponderance was noted, this was slight [ Table 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Recent large epidemiological surveys emphasise the importance of CSOM even when rates of otitis media with effusion or acute otitis media are not high. 6,7 Prospective studies in Australian Aboriginal infants have described early nasopharyngeal bacterial colonisation with Streptococcus pneumoniae, Haemophilus influenzae and Moraxella catarrhalis in the first few months of life. 9,10 This is associated with high rates of otitis media with effusion (OME) and frequent episodes of acute otitis media infections (acute otitis media without perforation).…”
Section: Epidemiology Of Common Ear Conditionsmentioning
confidence: 99%
“…13 Interestingly, crosssectional studies suggest that it may be possible to have high rates of CSOM without high rates of OME in some settings. 6,7 This needs to be confirmed through prospective birth cohort studies, with standardised assessment of middle-ear disease and nasopharyngeal colonisation.…”
Section: Epidemiology Of Common Ear Conditionsmentioning
confidence: 99%